Tourists’ perception on memorable tourism experience towards their revisit intentions to Islamic tourism destination in Shah Alam, Selangor / Mazlina Mahdzar. - Mahdzar, Mazlina (Universit Teknologi MARA Cawangan Selangor, 2019)
Islamic tourism has gained popularity among tourists and a huge potential for Malaysia to explore in the tourism industry. Muslims travelers are inclined to adhere to Islamic teachings which may, directly and indirectly, impact their decisions concerning leisure and travel plans. This study aims to examine the relationship linking tourists' memorable tourism experience attributes and their revisit intentions to Islamic tourism destination. Using convenience sampling, a total of 384 survey questionnaires were distributed to respondents visiting Islamic tourism attractions in Shah Alam and were used for data analysis. Regression results revealed that three Memorable Tourism Experience attributes have significant relationships with tourists’ revisit intention. These include hedonism experience, meaningfulness experience and social interaction. Of these three attributes, hedonism proved to have the most significant impact on tourists’ revisit intentions